(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to determine and analyze the influence of transformational leadership and organizational justice on employee job satisfaction at PT. PLN (Persero) UPT Simpang Empat. This research was conducted on employees at PLN (Persero) UPT Simpang Empat. This study is an associative study using a quantitative approach. The sample size for this study was 85 employees using a saturated sampling technique, a sampling technique where all members of the population are used as samples. This is often done when the population is relatively small, less than 100 people. The data analysis methods used in this study were validity and reliability tests, descriptive variable analysis, and multiple linear regression analysis. The results showed that 1) transformational leadership had a positive and significant effect on job satisfaction, 2) organizational justice had a positive and significant effect on job satisfaction, 3) leadership and organizational justice had a positive and significant effect on job satisfaction.